Autologous Fat Grafting in Hand Surgery: A Systematic Review - Brennon Henderson, BS; Caroline J. Cushman, BS; Ashley D. Price, BS; Lauren A. Hoffpauir, BS; Neil Jain, MD; Evan J. Hernandez, MBA; Anceslo Idicula, MD, MS; Brendan J. MacKay, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. Autologous fat grafting (AFG) has gained popularity in both cosmetic and reconstructive surgery, including hand surgery, due to its regenerative potential and dual benefits of enhancing aesthetics and function. This systematic review aims to evaluate the efficacy of AFG in treating various hand pathologies. Methods:. A systematic review was conducted following PRISMA guidelines. PubMed, Cochrane Library, and Embase databases were searched for studies published between January 2001 and October 2022 using the terms “(autologous fat grafting) AND (hand).” Of 224 studies identified, 14 met the inclusion criteria. These studies were analyzed based on study design, pathology treated, type of AFG used, and primary outcomes. Results:. The review included 14 studies: 9 prospective/retrospective studies, 3 case reports, and 2 randomized control trials. Digital ulcers related to systemic sclerosis and hand osteoarthritis were the most frequently treated pathologies. AFG was predominantly used to address symptoms/pain (71.4%), with aesthetics as a secondary benefit in 21.4% of cases. The studies reported improvements in pain, functionality, and patient satisfaction. However, the variability in techniques and outcomes limited the ability to perform a meta-analysis. Conclusions:. AFG shows promise as a minimally invasive treatment option for various hand pathologies, offering both symptomatic relief and aesthetic enhancement. Although initial findings are favorable, further high-quality studies are needed to standardize techniques and confirm long-term efficacy. The versatility and safety profile of AFG suggest it has the potential to become a widely adopted technique in hand surgery.